Determination of gap defect states in organic bulk heterojunction solar cells from capacitance measurements - Boix, Pablo P.; García-Belmonte, Germà; Muñecas, Udane; Neophytou, Marios; Waldauf, Christoph; Pacios, Roberto (My University, 2009)
Energy distributions [density-of-states (DOS)] of defects in the effective band gap of organic bulk heterojunctions are determined by means of capacitance methods. The technique consists of calculating the junction capacitance derivative with respect to the angular frequency of the small voltage perturbation applied to thin film poly(3-hexylthiophene) (P3HT) [6,6]-phenyl C61 -butyric acid methyl ester (PCBM) solar cells. The analysis, which was performed on blends of different composition, reveals the presence of defect bands exhibiting Gaussian shape located at E≈0.38 eV above the highest occupied molecular orbital level of the P3HT. The disorder parameter σ, which accounts for the broadening of the Gaussian DOS, lies within the range of 49-66 meV. The total density of defects results of order 1016 cm-3.
Keywords: Heterojunctions; Capacitance meters; Solar cells; peer reviewed